Managing Seasonal Influenza: Oseltamivir Treatment Policy in Indonesia? - Herman Kosasih; Arie Bratasena; Krisna Pangesti; Kanti Laras; Gina Samaan (Acta Medica Indonesiana)
To manage cases of avian influenza A/H5N1 virus infection and in anticipation of a pandemic triggered by this virus, Indonesia purchased and distributed oseltamivir to the government health facilities. Oseltamivir is an antiviral drug that was developed for the treatment of influenza infections. Disease surveillance and research suggests that seasonal influenza (A/H1N1, A/H3N2 or B) results in considerable morbidity and mortality in Indonesia, where over 15% of influenza-like illness and severe acute respiratory illness patients test positive for the influenza virus. Indonesia currently limits oseltamivir for the management of avian influenza A/ H5N1cases and in anticipation of a pandemic triggered by the A/H5N1 virus. We present the evidence for the use of oseltamivir in the treatment of seasonal influenza infections so that doctors have the option to prescribe the drug. We propose that the benefits of this approach will largely outweigh the risk of antiviral resistance. We recommend that oseltamivir be available for administration to patients with seasonal influenza infections especially for those hospitalized and for groups with high risk of complications and adverse outcomes. Overall, this will reduce morbidity and mortality of seasonal influenza.